Bus operation design with differential service types - Lai, Wei Joon (2014)
The purpose of this study is to promote the improvement of bus service in Singapore. One of the methods to improve the bus service is by loading the passengers at the high demand bus stops. This can be achieved by implementing the bus stop skipping scheme with different skipping model like deadheading, short turning & limited stop bus service. To further optimise this bus stops skipping scheme, various parameters such as waiting time, in-vehicle time (travel time) and the bus fare were examine and tested. Besides that, different model of waiting time is again analysed for the ease of the operator when deciding the bus’s fleet size and service frequency. Utility theory is applied and analysed for every new bus route model to determine the degree of satisfaction of the passengers. The finding was significant whereby the improvement of current bus service is necessary, in terms of travel route and waiting time. The suggested model shows if this strategy is implemented, there are higher possibilities that passengers will opt for the new services. Passengers will also be willing to accept the proposed bus route model, although there is an increase in bus fare of s$ 0.60 based on the Singapore fare structure system. It is also believed that this type of bus stop skipping service will greatly enhance the current bus services especially in the central business district zone.